Short-term monitoring of the Spanish government balance - Teresa Leal; Diego J. Pedregal; Javier J. Pérez (SERIEs - Journal of the Spanish Economic Association, 2011)
We construct multivariate, state-space mixed-frequencies models for the main components of the Spanish General Government sector made up of blocks for each one of its subsectors: Central Government, Social Security and aggregate of Regional and Local government sectors. Each block is modelled through its total revenue and expenditure categories, and encompasses a number of indicators, depending on data availability. The mixed-frequencies approach is particularly relevant for the case of Spain, given its institutional set-up and the specific data availability for the different subsectors. All in all, we provide models detailed enough in coverage, while at the same time manageable, to be used: (1) for real-time monitoring of fiscal policies with a focus on quarterly developments of the General Government sector, (2) for the monitoring of general government sub-sectors for which intra-annual data coverage is limited (Regional and Local governments), (3) to bridge (translate) into National Accounts availablemonthly information for the subsectors of the general government.
Keywords: C53; E6; H6; 330; fiscal forecasting; fiscal policies; mixed frequency data; Kalman filter; Öffentlicher Sektor; Zustandsraummodell; Prognose; Spanien